Estudo do perfil imunológico em crianças e adolescentes com Leucemia Linfoblástica Aguda no Amazonas - Carvalho , Maria do Perpetuo Socorro Sampaio (2015)
Current proposals treatment of children and adolescents with acute lymphoblastic leukemia enable increased survival, increase the chances of cure of patients and seek to reduce late effects related to therapy and the Brazilian Group of Treatment of Leukemia Acute Lymphoblastic of Children and Adolescents - GBTLI proposes regimens categorized by prognostic criteria for relapse risk of this condition. These patients have immunological profile changed by the disease itself and held by therapy which can contribute to the response and complications during treatment. The study aimed to describe the cellular immune response profile of cytokines, chemokines and identify possible immune biomarkers according to the treatment-risk group with GBTLI LLA-2009 protocol in patients with ALL aged zero to minor 18 years during induction therapy. The methodology used was not experimental, longitudinal, prospective cohort. Patients were stratified by risk group and analyzed during induction therapy in four stages: the diagnosis (D0), the eighth day (D8), the fifteenth day (D15) and thirty-fifth day (D35). The control group performed only one evaluation. The immune response was characterized by analysis of total lymphocytes, T lymphocytes (LT), LT CD4+, LT CD8+, NK cells, NKT cells and Treg lymphocytes CD4+/CD25+/FoxP3+) and serum cytokines Th1, Th2, Treg and Th17 and serum chemokines MCP-1, RANTES, IL-8, IP-10 and MIG by flow cytometry. In the study it was observed that the diagnosis LT-were reduced in the first fifteen days of induction. IL-2, IFN-γ and IL-4 were reduced to their production, but not significant. The CD4+ and CD8+ were increased throughout the induction. Treg lymphocytes increased only on D15 and D35. NK cells decreased at D0, D15 and D35, and NKT cell only on D0 and in particular RA group. IL-6 was increased in D0 and IL-10 at D0 and D8. The TNF-α presented itself decreased throughout the induction. RANTES was decreased in D0, D15 and D8 and MIG decreased from D8 until the end of induction. MCP-1 decreased the D15 and IL-8 increased in RH group in D35. In interactions networks, Treg lymphocytes on D0 interacted with MCP-1, MIG and IP-10 and IL-10 with IL-8, MCP-1 and MIG and lost their interactions in D35. These results suggest that patients with ALL at diagnosis have immune dysregulation. The predominance of interactions immunoregulatory response by IL-10 and Treg lymphocytes with cytokines / chemokines may indicate a decrease or loss of its action at the end of induction, with a predominance of the inflammatory response, which suggests tumor control and bone marrow recovery